Social Informatics Second International Conference, SocInfo 2010, Laxenburg, Austria, October 27-29, 2010. Proceedings - Bolc, Leonard; Makowski, Marek; Wierzbicki, Adam.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the Second International Conference on Social Informatics, SocInfo 2010, held in Laxenburg, Austria, in October 2010. The 17 revised full papers presented were carefully reviewed and selected from numerous submissions and feature both the theoretical social network analysis and its practical applications for social recommendation as well as social aspects of virtual collaboration, ranging from social studies of computer supported collaborative work, to the study of enhancements of the Wiki technology. Further topics are research on Webmining, opinion mining, and sentiment analysis; privacy and trust; computational social choice; and virtual teamwork.
Case-Based Team Recommendation -- Toward a Behavioral Approach to Privacy for Online Social Networks -- A Meta Model for Team Recommendations -- Node Degree Distribution in Affiliation Graphs for Social Network Density Modeling -- Achieving Optimal Privacy in Trust-Aware Social Recommender Systems -- First-Use Analysis of Communication in a Social Network -- Label-Dependent Feature Extraction in Social Networks for Node Classification -- Computing ?-Efficient Cost Allocations for Unbalanced Games -- Recommendation Boosted Query Propagation in the Social Network -- Social Manipulation of Online Recommender Systems -- Bicriteria Models for Fair and Efficient Resource Allocation -- Dynamic Context-Sensitive PageRank for Expertise Mining -- Trust-Based Peer Assessment for Virtual Learning Systems -- Exponential Ranking: Taking into Account Negative Links -- Social Email: A Framework and Application for More Socially-Aware Communications -- Measuring Message Propagation and Social Influence on Twitter.com -- SocialWiki: Bring Order to Wiki Systems with Social Context.
Keywords: Computer science; Computer Communication Networks; Data mining; Information systems; Artificial intelligence; Social sciences -- Data processing; Computer Science; Information Systems Applications (incl.Internet).; Computer Communication Networks; Artificial Intelligence (incl. Robotics).; Computer Appl. in Social and Behavioral Sciences; User Interfaces and Human Computer Interaction; Data Mining and Knowledge Discovery